Giant Splenic Artery Pseudoaneurysm - Goldberg, Ross Frederick; Maley, Warren; Kennedy, Eugene P.; Yeo, Charles J.; Lavu, Harish (Journal of gastrointestinal surgery, 2011)
Background Giant splenic artery pseudoaneurysms (≥5 cm in size) are rare entities. We document the successful operative management of one of the largest splenic artery pseudoaneurysms (18 cm) ever reported as well as review the world literature on the subject. Method Our literature review identified 160 cases of splenic artery pseudoaneurysm in the last 43 years. These ranged in size from 0.3 to 17 cm, and of these, 18 (11%) were 5 cm or larger. The majority of patients underwent treatment, either endovascularly or with open surgery, and their outcomes were independent of presenting symptoms or size. Results Giant splenic artery pseudoaneurysms are uncommon, most often caused by pancreatitis, trauma, or iatrogenic etiologies and typically present with vague constitutional symptoms, or occasionally with hemorrhage. Most can be treated endovascularly, though in our case this was not possible due to the presence of celiac artery occlusion with retrograde filling of the pseudoaneurysm from superior mesenteric artery collaterals. Ultimately, we opted for an open technique, with supraceliac aortic control prior to manipulation and resection of the pseudoaneurysm. Conclusion Our recommendation is that splenic artery pseudoaneurysms should be repaired when encountered, regardless of aneurysm size at presentation.